Marketing Efficiency and Value Chain Analysis: The Case of Garlic Crop in Bangladesh - Hasan, Md. Kamrul; Khalequzzaman, K. M. (American Journal of Trade and Policy, 2017)
Garlic is a highly profitable crop and is largely used both in medicinal and culinary purposes. The study was undertaken to determine marketing system, marketing cost, marketing margin, marketing efficiencies and to examine the value chain of garlic aiming to determine the value addition in different steps of garlic marketing. A purposive and simple randomized sampling procedure was used in selecting primary data. Marketing margin, profit, efficiency ratio, value addition etc. were calculated by different relevant equations and formulas. Four major marketing channels were identified for domestic produced garlic marketing. Channel-3 was the most important supply chain through which 40% domestic produced garlic reaches to consumers. Marketing margin and profit were the highest in retailer than those of other intermediaries. Out of four marketing channel, Channel-2 was more efficient than those of other channels. Six actors like; farmer, local trader, trader, commission agent, wholesaler, retailer and consumer are identified who are involved in the garlic value chain activities. Retailer added highest amount of value per unit of garlic and that of the lowest in wholesaler. Eleven marketing problem were identified, among them price fluctuation, high transport cost and lack of loan facilities were the major problem. It is therefore, recommended that Government intervention is urgent necessary to stabilize the price of garlic, loan facilities should be provided to the intermediaries and transportation cost should be kept reasonable.
Keywords: Garlic; marketing system; marketing efficiency; value chain